2020
DOI: 10.1177/0969141320974711
|View full text |Cite
|
Sign up to set email alerts
|

The impact of episodic screening interruption: COVID-19 and population-based cancer screening in Canada

Abstract: Background Population-based cancer screening can reduce cancer burden but was interrupted temporarily due to the COVID-19 pandemic. We estimated the long-term clinical impact of breast and colorectal cancer screening interruptions in Canada using a validated mathematical model. Methods We used the OncoSim breast and colorectal cancers microsimulation models to explore scenarios of primary screening stops for 3, 6, and 12 months followed by 6–24-month transition periods of reduced screening volumes. For breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
172
2
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(196 citation statements)
references
References 11 publications
(18 reference statements)
11
172
2
11
Order By: Relevance
“…These results confirm the estimates obtained through the mathematical models of Yong et al 15 and Sharpless 16 in terms of increased advanced stages at diagnosis. Additionally, since treatment of more advanced cancers generally involves more widespread use of systemic therapy and invasive surgery, we may also conclude that these delays in cancer diagnosis could be associated with increased morbidity and higher costs for our national health system.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results confirm the estimates obtained through the mathematical models of Yong et al 15 and Sharpless 16 in terms of increased advanced stages at diagnosis. Additionally, since treatment of more advanced cancers generally involves more widespread use of systemic therapy and invasive surgery, we may also conclude that these delays in cancer diagnosis could be associated with increased morbidity and higher costs for our national health system.…”
Section: Discussionsupporting
confidence: 90%
“…14 Although asymptomatic women who have skipped their screening mammogram because of COVID-19 are recommended to reschedule the check preferably within 3 months, 11 the real impact of temporary mammographic screening suspension on BC outcomes remains uncertain. Yong et al 15 have recently estimated the long-term clinical impact of BC screening interruptions in Canada using a validated mathematical model. The authors found that a 3-month interruption in BC screening could increase cases diagnosed at advanced stages and cancer deaths in 2020-2029.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 These disruptions are expected to result in an excess of advanced cancer diagnoses and deaths in the coming years. 2 , 3 , 4 , 5…”
Section: Introductionmentioning
confidence: 99%
“…Their interruptions or even delays can lead to severe consequences in the coming years for both patients' outcomes and financial sustainability of healthcare systems. 4,5 Regarding future research outlooks, it will be important to comprehensively evaluate the overall consequences of the COVID-19 pandemic on surgical oncology practice, also to estimate its potential impact on cancer care in the coming years and design possible coping strategies.…”
mentioning
confidence: 99%